PKM Human Resources Empowerment to Improve Employee Performance at Citra Lestari UMKM, Binor Village, Paiton District - Deddy Junaedi; Nita Nurmalia Oktaviani; Serli Hikmah; Siti Faiqah; Uhiya Ayu Ningsih; Yuni Safara (Abdimas Paspama, 2023)
Vegetable sticks are a processed product made from spinach which can then be used as a snack or can be called a snack. The obstacles faced by Citra Lestari UMKM are related to their human resources, namely : 1) Employees who are elderly and less productive, 2) Low employee skills, and 3) Lack of management understanding. One solution to overcome the obstacles that exist within Citra Lestari UMKM is to hold socialization in the workplace, as well as mentoring and service programs for employees at Citra Lestari UMKM. By providing opportunities for employees to learn new things, especially those related to skills, employees will be better prepared to handle work challenges and contribute more to business business processes. In implementing PKM activities at Citra Lestari UMKM, the service team has several plans/stages that have been prepared, namely starting from the preparation, observation, training, solution application, supervision and evaluation stages.